Population Structure and Regeneration Status of Woody Plant Species in Tulu Korma Dry Afromontane Forest, West Shewa Zone, Oromia, Ethiopia - Diriba Deressa; Meseret C. Egigu; J. M. Sasikumar (Scientifica)
A study was conducted on Tulu Korma afromontane forest to assess woody plant species’ population structure and natural regeneration status. Data were collected from 52 main quadrats of 400 m2 for mature woody species and 260 subplots of 25 m2 for seedlings and saplings. All live woody plant species were recorded with their densities, heights, and DBH. Frequency, basal area, importance value, and Shannon–Wiener diversity indices were computed. A total of 101 species that belonged to 45 families were documented. Diversity and evenness indices were 3.44 and 0.7, respectively. Combined density of woody species of all developmental stages was 4971 stems ha−1 of which 39, 32, and 28% were with DBH < 3.5 cm (seedlings), between 2 and 10 cm (saplings), and >10 cm (mature wordy species), respectively. The total basal area of individuals with DBH ≥ 3.5 cm was 116.18 m2 ha−1. Olea europaea and Podocarpus falcatus were the most dominant species. About 41.58% of the species had IVI < 1. Population structure based on combined densities revealed that density of seedling > sapling > mature individuals, suggesting healthy population structure and good regeneration. On individual basis, however, species showed different patterns of population structure of which 12, 51, and 37% species showed good, fair, and poor regenerations, respectively. Species with least IVI and poor regeneration should be given conservation priority.